The growth suppressing effects of Girinimbine on Hepg2 involve induction of apoptosis and cell cycle arrest. - Syam, Suvitha; Abdul, Ahmad Bustamam; Md.Sukari, Mohd. Aspollah; Mohan, Syam; Abdelwahab, Siddig Ibrahim; Tang , Sook Wah (MDPI, 2011)
Murraya koenigii is an edible herb widely used in folk medicine. Here we report that girinimbine, a carbazole alkaloid isolated from this plant, inhibited the growth and induced apoptosis in human hepatocellular carcinoma, HepG2 cells. The MTT and LDH assay results showed that girinimbine decreased cell viability and increased cytotoxicity in a dose-and time-dependent manner selectively. Girinimbine-treated HepG2 cells showed typical morphological features of apoptosis, as observed from normal inverted microscopy and Hoechst 33342 assay. Furthermore, girinimbine treatment resulted in DNA fragmentation and elevated levels of caspase-3 in HepG2 cells. Girinimbine treatment also displayed a time-dependent accumulation of the Sub-G0/G1 peak (hypodiploid) and caused G0/G1-phase arrest. Together, these results demonstrated for the first time that girinimbine could effectively induce programmed cell death in HepG2 cells and suggests the importance of conducting further investigations in preclinical human hepatocellular carcinoma models, especially on in vivo efficacy, to promote girinimbine for use as an anticancer agent against hepatocellular carcinoma.